Pengembangan Bahan Ajar BIPA Daring Tingkat Pemula Rendah - Ahmad Rofiuddin; Gatut Susanto; Didin Widyartono; Sultan Sultan; Helmi Muzaki; Pensri Panich (Ranah: Jurnal Kajian Bahasa, 2021)
The aim of this study is to develop Indonesian language teaching online materials as a Foreign Language (BIPA) which are suitable for beginner low level learners. This research is conducted in Malang in 2020. The procedure in this study uses the (Gall et al., 2007). The characteristics of the product consist of thirteen lessons that are used for online BIPA learning. Each lesson is developed based on actual topics according to beginner low level learner needs. The actual topics cover introduction, campus, home, office, canteen, park, and market. The variety of Indonesian uses in this teaching material is communicative variety. In addition, this teaching material is equipped with English as an complementary language. Based on the use test on the aspects of content, language, and presentation order, it can be concluded that online BIPA teaching material for beginner low-level learners has high feasibility. AbstrakPenelitian ini bertujuan untuk menghasilkan bahan ajar Bahasa Indonesia bagi Penutur Asing (BIPA) daring yang memiliki kelayakan untuk digunakan bagi pebelajar tingkat pemula rendah. Penelitian ini dilakukan di Malang pada tahun 2020. Prosedur yang digunakan adalah model (Gall et al., 2007). Karakteristik bahan ajar yang dihasilkan terdiri atas tiga belas unit pelajaran yang digunakan untuk pembelajaran BIPA secara daring. Tiap unit pelajaran dikembangkan bertumpu pada topik aktual sesuai dengan kebutuhan pebelajar tingkat pemula rendah. Topik-topik aktual tersebut antara lain tentang perkenalan, kampus, rumah, kantor, kantin, taman, dan pasar. Ragam bahasa Indonesia yang digunakan dalam bahan ajar ini ragam komunikatif. Selain itu, bahan ajar ini difasilitasi bahasa bantu bahasa Inggris. Berdasarkan uji pakai terhadap aspek isi, bahasa, dan struktur penyajian dapat disimpulkan bahwa bahan ajar BIPA daring untuk pebelajar tingkat pemula rendah daring ini memiliki kelayakan tinggi.